2014
DOI: 10.1002/uog.13358
|View full text |Cite
|
Sign up to set email alerts
|

Association of Doppler parameters with placental signs of underperfusion in late-onset small-for-gestational-age pregnancies

Abstract: Objective To elucidate the association between Doppler parameters and histological signs of placental underperfusion in late-onset small-for-gestational-age (SGA) babies. Methods 1.1-3.7)) and decreased UVBF normalized to estimated fetal weight (P = 0.027; OR 0.97 (95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 56 publications
(61 reference statements)
8
55
0
1
Order By: Relevance
“…These cases are explained by a lower degree of placental dysfunction, which is insufficient to severely compromise growth or manifest changes in fetal Doppler [44,45,46]. However, this dysfunction may still be sufficient to generate signs of chronic hypoxia and fetal redistribution, which might lead to increased perinatal morbidity and mortality [47].…”
Section: Discussionmentioning
confidence: 99%
“…These cases are explained by a lower degree of placental dysfunction, which is insufficient to severely compromise growth or manifest changes in fetal Doppler [44,45,46]. However, this dysfunction may still be sufficient to generate signs of chronic hypoxia and fetal redistribution, which might lead to increased perinatal morbidity and mortality [47].…”
Section: Discussionmentioning
confidence: 99%
“…The UA Doppler failed to identify fetal compromise in a significant number of late SGA fetuses [32]. Additionally, in fetuses with L-IUGR the placental insufficiency seems not to be reflected in UA Doppler [37].…”
Section: L-iugrmentioning
confidence: 85%
“…UA Doppler and the sequence of Doppler modifications in multiple fetal vessels are not reliable for the fetal surveillance [4,37]. Recent papers focus on Doppler markers of cerebral vasodilatation that seems to be a landmark of L-IUGR.…”
Section: L-iugrmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, it would have been interesting to have histological information of the placental tissues. A mounting body of evidence shows that signs of placental underperfusion, both maternal and fetal, are found in most late-onset IUGR and that these signs correlate with prenatal Doppler status [26], and perinatal [27] and long-term neurological [26] outcomes. It has also been reported that such placental signs are associated with an antiangiogenic profile [28].…”
Section: Discussionmentioning
confidence: 99%